Preparation and characterization of porous fly ash/NiFe2O4 composite: promising adsorbent for the removal of congo red dye from aqueous solution - Sonar, Shilpa K.; Niphadkar, Prashant S.; Mayadevi, S.; Joshi, Praphulla N. (Materials Chemistry and Physics, 2014)
A series of fly ash/NiFe2O4 composites were prepared using fly ash and aqueous solutions of Ni, Fe nitrate salts and NaOH by co-precipitation followed by calcination method. The % mass ratio of fly ash: NiFe2O4 was varied in the range of 0:100 to 100:0. Samples were characterized by powder XRD, SEM, FTIR and N-2 adsorption-desorption measurements. These samples were further evaluated for their adsorptive performance in removal of Congo red (CR) dye from an aqueous solution. In all the composites, spinel nickel ferrite phase was found to be capable to get anchored with the fly ash surface and exhibited more crystalline nature as compared to pure NiFe2O4 phase. The BET surface area and porous character of the composite were found to increase with the decrease in the contribution of the fly ash, reach to maximum and then decreases on further decrease in fly ash. The composite having % mass ratio of fly ash: NiFe2O4 = 50:50 exhibited maximum CR adsorption from the aqueous solution on account of the higher BET surface area, more porous character, favorable condition for diffusion of dye molecules and combined effect of chemisorption and physisorption. Under optimum conditions, it has shown the recyclability with adsorption capacity of the magnitude 23.33 mg g(-1), which is much higher than individual fly ash, NiFe2O4 and other composites. The sorption data provided good fit with pseudo-second order kinetic model. The analyses of the adsorption data indicated that, the Langmuir model provides better correlation with the experimental data. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Composite material; Electron microscopy (SEM); Inorganic compounds; powder diffraction; Precipitation